HIV-1 tuberculosis-associated immune reconstitution inflammatory syndrome - Lai, Rachel P. J. (Springer Berlin Heidelberg, 2015)
Patients co-infected with HIV-1 and tuberculosis (TB) are at risk of developing TB-associated immune reconstitution inflammatory syndrome (TB-IRIS) following commencement of antiretroviral therapy (ART). TB-IRIS is characterized by transient but severe localized or systemic inflammatory reactions against Mycobacterium tuberculosis antigens. Here, we review the risk factors and clinical management of TB-IRIS, as well as the roles played by different aspects of the immune response in contributing to TB-IRIS pathogenesis.